A preparation method and application of fibrous LSCO conductive ceramic material
The fiber-type LSCO conductive ceramic material is prepared by sol-gel combined with vapor spinning, which solves the problem of poor processing performance of LSCO materials in the prior art, achieves efficient and low-cost preparation, and improves the performance and production efficiency of electrical contact materials.
Patent Information
- Application Number
- CN202310399820.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-04-07
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2043-04-07
AI Technical Summary
In the prior art When preparing silver-based electrical contact materials, the processing performance of the perovskite structure's high-temperature superconducting ceramic La1-xSrxCoO3-δ (LSCO) material has poor processing performance and is unable to achieve industrial production.
The synthesis method of sol-gel combined with vapor spinning is used to prepare fiber-type LSCO conductive ceramic materials, avoid the use of polymers as fiber molding agents, and synthesis of fiber materials with excellent conductivity by regulating the reaction conditions and vapor spinning parameters of the precursor solution.
It realizes efficient preparation of fiber-type LSCO conductive ceramic materials, reduces costs, improves yields, improves the electrical and processing properties of electrical contact materials, and lays the foundation for its industrial production.
Smart Images

Figure CN117003292B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a preparation technology of conductive ceramic fibers, and in particular to a fibrous La 1-x Sr x CoO 3-δ Preparation method of conductive ceramic material, fibrous La 1-x Sr x CoO 3-δ It can be used as a reinforcement phase to prepare silver-based electrical contact materials. Background Art
[0002] In the context of the electrical age, power facilities and electronic and electrical products have developed rapidly, making the application scope of electrical contact materials wider and wider, and the amount used is also increasing. Among electrical contact materials, silver-based composite materials are widely used in components such as circuit breakers and contactors because of their good resistance to welding, electrical conductivity, low and stable contact resistance. Conductive ceramics can be used as an ideal choice for the second phase of electrical contact composite materials because of their advantages such as metallic conductivity, high temperature resistance and good mechanical properties. One of the perovskite-structured high-temperature superconducting conductive ceramics, La 1-x Sr x CoO 3-δ (hereinafter referred to as LSCO), which has low resistivity and adjustable structural performance parameters, has been studied and applied to electrical contact composite materials. It has excellent electrical conductivity and suitable hardness. However, the processing performance of Ag / LSCO electrical contact materials is poor and cannot be industrialized. Therefore, LSCO conductive ceramics can be regulated into fiber morphology to further enhance its conductivity. The fiber toughening mechanism (fiber pull-out, debonding, and bridging toughening) can be used to increase the fracture energy of Ag / LSCO electrical contact materials, thereby improving their processing performance and solving the problem of their inability to be industrialized.
[0003] At present, the methods for preparing nanofibers include template synthesis, self-assembly, stretching and electrospinning. Among them, electrospinning has become one of the main ways to effectively prepare nanofiber materials due to its advantages of simple preparation equipment, a wide variety of spinnable materials and controllable process. However, it requires polymers (PEO, PVA, PVP, etc.) as fiber forming agents, and parameters such as the molecular weight and concentration of polymers are important indicators that affect the fiber diameter and quality, resulting in high costs and low yields. Compared with traditional electrospinning technology, the rate of producing nanofiber materials with air spinning technology is several times higher than that of conventional electrospinning technology. It can achieve large-scale production while regulating the fiber morphology and diameter, but the current process also requires polymers as fiber forming agents. Summary of the invention
[0004] The technical problem to be solved by the present invention is to provide a method for preparing a fiber-type LSCO conductive ceramic by combining sol-gel with air spinning, so that polymer as a fiber forming agent is no longer used, and the synthesis method is simple, low-cost and high-production rate. The product prepared by the method can be used to improve the electrical properties and processing properties of electrical contact materials, and the prepared fiber-type LSCO conductive ceramic is used as the second phase of the silver-based electrical contact composite material to enhance the conductivity and improve the processing properties, thereby laying a foundation for its industrial production.
[0005] To solve the technical problem, the specific steps of the solution of the present invention are as follows:
[0006] (1) Preparation of precursor solution by sol-gel method
[0007] Press La 3+ :Sr 2+ :Co 3+ The molar ratio of the precursors is 1:4:5 to 4:1:5. The precursors are weighed and added into deionized water to prepare a mixed solution with a metal ion concentration of 0.5 to 2.0 mol / L, and stirred with a magnetic force until completely dissolved.
[0008] The complexing agent is weighed according to the molar ratio of the complexing agent to the metal ion of 1 to 5:1, added to the above mixed solution, and ammonia water is added to adjust the pH value to 7 to 10. The mixture is stirred in a water bath at 50 to 80° C. for 3 to 10 hours, then stirred at room temperature for 10 to 20 hours, and aged for 24 to 48 hours to obtain a precursor solution with a certain viscosity (0.2 to 0.9 Pa·s) and surface tension (30 to 40 mN / m).
[0009] (2) Air spinning
[0010] The precursor solution is used as a spinning solution for gas spinning, the inner diameter of the needle is 0.1-1.5 mm, the syringe injection speed is 0.3-7 mL / h, the atmosphere is air, the air flow rate is 50-200 L / min, the collection distance is 50-200 cm, and a heating lamp is used to accelerate the evaporation of the liquid phase to obtain the precursor fiber.
[0011] (3) Calcination treatment
[0012] The precursor fiber is pre-sintered at a temperature of 150-200° C. for 1-5 hours, and then calcined in air at a temperature of 700-900° C., a heating rate of 1-5° C. / min, and a holding time of 1-3 hours to obtain a black fibrous LSCO conductive ceramic material.
[0013] As a preferred embodiment of the present invention, the La 3+ The precursor is lanthanum nitrate, Sr 2+ The precursor is strontium nitrate, Co 3+The precursor is cobalt nitrate.
[0014] As a preferred embodiment of the present invention, the complexing agent in step (1) is one or more of maleic acid, acrylic acid, citric acid, ethylenediaminetetraacetic acid (EDTA), and glucose.
[0015] As a preferred embodiment of the present invention, the complexing agent is maleic acid and acrylic acid, wherein the molar ratio is maleic acid:
[0016] Acrylic acid:metal ion=1.5:1:1.
[0017] As a preferred embodiment of the present invention, in step (1), ammonia water is added to adjust the pH value to 9.5, stirred in a 70°C water bath for 4 hours, stirred at room temperature for 12 hours, and aged for 24 hours to obtain a precursor solution with certain fluidity and viscosity.
[0018] As a preferred embodiment of the present invention, in step (2), a needle with an inner diameter of 0.5 mm is used for air spinning, the syringe injection speed is 3 mL / h, the air flow rate is 80 L / min, and the collection distance is 50 cm.
[0019] As a preferred embodiment of the present invention, the pre-sintering temperature in step (3) is 180°C, the holding time is 3h, the calcining temperature is 700°C, the holding time is 3h, and the heating rate is 1°C / min.
[0020] The present invention further provides an application of the prepared LSCO conductive ceramic fiber material, using silver powder as a matrix phase and fibrous LSCO conductive ceramic material as a reinforcement phase to prepare Ag / LSCO electrical contact material by a molding and sintering process.
[0021] Furthermore, the specific implementation method of the application is: weigh silver powder and the above-mentioned fibrous LSCO conductive ceramic material in a mass ratio of 86:14 to 92:8, add them into a ball mill, the mass ratio of grinding balls to materials is 2 to 5:1, the rotation speed is 150 to 500 rpm, and mix for 3 to 6 hours to obtain a silver-based composite material; after pressing and molding at 900 to 1200 MPa, sintering is performed at a sintering temperature of 700 to 900°C and a holding time of 4 to 8 hours, and then re-pressing and re-firing are performed through the same pressing and sintering process to obtain Ag / LSCO electrical contact material.
[0022] As a preferred embodiment of the present invention, the mass ratio of silver powder to LSCO conductive ceramic fiber material is 90:10, the ball material mass ratio is 4:1, the rotation speed is 300 rpm, the silver-based composite material is obtained by mixing for 4 hours, the pressing pressure is 1100 MPa, the sintering temperature is 880°C, and the insulation time is 6 hours to finally obtain Ag / LSCO electrical contact material.
[0023] The inventive principle of the present invention is:
[0024] LaCoO 3 With standard ABO 3 Type perovskite structure. After doping with strontium, the radius of strontium ions is slightly larger than that of lanthanum ions, so the original perovskite structure is distorted, but it does not destroy the original structure. LSCO has rich electrical, magnetic, optical and other properties due to its complex and changeable structure. Its lattice constant and crystal form will change with temperature and strontium doping amount. For example, with the increase of strontium doping amount, the conductivity of LSCO will increase first, and then gradually decrease after reaching a maximum value. Studies have shown that LSCO will decompose under the action of high-temperature arc, which helps to absorb arc energy, and its decomposition products will remain in the molten pool, which is beneficial to improve the viscosity and surface tension of the molten pool, reduce droplet splashing, and improve the arc erosion resistance of electrical contact materials. Ag / LSCO electrical contact material can be studied and developed as a new type of electrical contact material because of its excellent conductivity, suitable hardness, low and stable contact resistance, strong resistance to welding and arc erosion.
[0025] Gas spinning technology does not require an external electric field to promote fiber formation, so it does not require the solution to have conductive properties, that is, it is not necessary to use a polymer as a fiber forming agent, but the precursor solution is required to have a certain viscosity and a small surface tension. Based on the principle of the sol-gel method, the viscosity and surface tension of the solution can be adjusted by changing the water bath stirring temperature and aging time of the sol-gel method, the type of complexing agent and its ratio with metal ions, so as to meet the requirements of gas spinning. Based on the fiber toughening and particle transmission channel mechanism, the reinforcing phase is designed to be a fiber morphology to increase the fracture energy and improve the processing performance of the electrical contact material; the conductive ceramic fiber has excellent electron and phonon transmission characteristics, and using it as a second phase can enhance the electrical and thermal conductivity of the electrical contact material. The present invention utilizes the sol-gel method combined with gas spinning technology, and synthesizes black LSCO conductive ceramic fiber materials by adjusting the reaction conditions of the precursor solution, gas spinning parameters and sintering temperature and other process parameters, and prepares LSCO conductive ceramic fiber reinforced silver-based composite materials through a molding and sintering process. In the present invention, the water bath stirring temperature and aging time, the ratio of the complexing agent to the metal ion, the air spinning parameters such as the needle inner diameter, the gas flow rate, and the sintering parameters such as the heating rate and the holding time will affect the morphology, size and production efficiency of the fiber. The water bath stirring temperature and aging time and the ratio of the complexing agent to the metal ion will affect the viscosity and surface tension of the precursor solution, and then affect the fiber diameter; the air spinning parameters such as the needle inner diameter and the gas flow rate will affect the fiber production rate and stability; the sintering parameters such as the heating rate and the holding time will affect the final quality of the fiber.
[0026] Innovations and beneficial effects of the present invention:
[0027] 1. Compared with the current electrospinning method and gas spinning method, the present invention synthesizes a precursor solution with a certain viscosity and surface tension by combining the sol-gel method, and no longer uses polymers as fiber forming agents, thereby reducing costs and improving productivity.
[0028] 2. Compared with the current hydrothermal method and electrospinning method, the present invention utilizes the gas spinning method to synthesize the precursor fiber by regulating the reaction conditions of the precursor solution and the gas spinning parameters, and obtains the LSCO conductive ceramic fiber by calcination treatment. It does not require the long reaction time and high temperature and high pressure conditions of the hydrothermal method. The production efficiency is several times higher than that of the electrospinning method. It has the characteristics of mild production conditions, high production efficiency and low cost, and is suitable for industrial production.
[0029] 3. Compared with granular and microspherical LSCO conductive ceramic reinforcement phases, the Ag / LSCO electrical contact material prepared using fibrous LSCO conductive ceramic material in the present invention has better processing performance and electrical and thermal conductivity, and can significantly improve the production efficiency and electrical life of the electrical contact material.
[0030] 4. The products prepared by the method of the present invention can be used in aerospace, new energy vehicles, high-power charging piles and other fields, and have broad prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 This is the XRD pattern of the LSCO conductive ceramic fiber synthesized in Example 1.
[0032] Figure 2 This is the SEM image of the LSCO conductive ceramic fiber synthesized in Example 1. DETAILED DESCRIPTION
[0033] The implementation of the present invention is exemplarily described below through specific embodiments.
[0034] Example 1
[0035] In this example, La 0.5 Sr 0.5 CoO 3 The steps of fiber are:
[0036] (1) Preparation of precursor solution
[0037] Press La 3+ :Sr 2+ :Co 3+Lanthanum nitrate, strontium nitrate and cobalt nitrate are weighed and added into deionized water to prepare a mixed solution with a metal ion concentration of 1.0 mol / L, and magnetic stirring is performed until the mixture is completely dissolved; a complexing agent is weighed and added into the mixed solution, wherein the complexing agent is maleic acid and acrylic acid, wherein the molar ratio of maleic acid: acrylic acid: metal ion is 1.5:1:1, and ammonia water is added to adjust the pH value to 9.5, and the mixture is stirred in a water bath at 70°C for 4 hours, stirred at room temperature for 12 hours, and aged for 24 hours to obtain a precursor solution with a viscosity of 0.4 Pa·s and a surface tension of 36 mN / m.
[0038] (2) Air spinning
[0039] The precursor solution was used as a spinning solution for gas spinning, with a needle inner diameter of 0.5 mm, a syringe injection speed of 3 mL / h, an air atmosphere, an air flow rate of 80 L / min, and a collection distance of 50 cm to obtain a precursor fiber.
[0040] (3) Calcination treatment
[0041] The precursor fiber was pre-sintered at 180° C. for 3 h, and then calcined in air at 700° C. for 3 h at a heating rate of 1° C. / min to obtain a black fibrous LSCO conductive ceramic material.
[0042] Preparation of Ag / LSCO electrical contact materials
[0043] Silver powder and the above-mentioned fibrous LSCO conductive ceramic material are weighed in a mass ratio of 90:10, added into a ball mill, the mass ratio of grinding balls to materials is 4:1, the rotation speed is 300 rpm, and mixed for 4 hours to obtain a silver-based composite material; after pressing and molding at 1100 MPa, sintering is performed at a sintering temperature of 880°C and a holding time of 6 hours, and then re-pressing and re-firing are performed through the same pressing and sintering process to obtain Ag / LSCO electrical contact material.
[0044] Example 2
[0045] In this example, La 0.2 Sr 0.8 CoO 3 The steps of fiber are:
[0046] (1) Preparation of precursor solution
[0047] Press La 3+ :Sr 2+ :Co 3+Lanthanum nitrate, strontium nitrate and cobalt nitrate are weighed in a molar ratio of 1:4:5, added into deionized water to prepare a mixed solution with a metal ion concentration of 0.5 mol / L, and magnetically stirred until completely dissolved; a complexing agent is weighed and added into the above mixed solution, the complexing agent is citric acid and ethylenediaminetetraacetic acid (EDTA), wherein the molar ratio of citric acid:EDTA:metal ion is 3:2:1, and ammonia water is added to adjust the pH value to 10, stirred in a water bath at 50°C for 6h, stirred at room temperature for 10h, aged for 36h, and a precursor solution with a viscosity of 0.2Pa·s and a surface tension of 30mN / m is obtained.
[0048] (2) Air spinning
[0049] The precursor solution was used as a spinning solution for gas spinning, with a needle inner diameter of 0.1 mm, a syringe injection speed of 0.3 mL / h, an air atmosphere, an air flow rate of 50 L / min, and a collection distance of 100 cm to obtain a precursor fiber.
[0050] (3) Calcination treatment
[0051] The precursor fiber was pre-sintered at 150° C. for 5 h, and then calcined in air at 800° C. for 2 h at a heating rate of 3° C. / min to obtain a black fibrous LSCO conductive ceramic material.
[0052] Preparation of Ag / LSCO electrical contact materials
[0053] Silver powder and the above-mentioned fibrous LSCO conductive ceramic material are weighed in a mass ratio of 86:14, added into a ball mill, with a mass ratio of grinding balls to materials of 2:1, a rotation speed of 200 rpm, and mixed for 6 hours to obtain a silver-based composite material; after pressing and molding at 1200 MPa, sintering is performed at a sintering temperature of 900°C and a holding time of 4 hours, and then re-pressing and re-firing are performed through the same pressing and sintering process to obtain an Ag / LSCO electrical contact material.
[0054] Example 3
[0055] In this example, La 0.8 Sr 0.2 CoO 3 The steps of fiber are:
[0056] (1) Preparation of precursor solution
[0057] Press La 3+ :Sr 2+ :Co 3+Lanthanum nitrate, strontium nitrate and cobalt nitrate are weighed in a molar ratio of 4:1:5, added into deionized water to prepare a mixed solution with a metal ion concentration of 2.0 mol / L, and magnetically stirred until completely dissolved; a complexing agent is weighed and added into the above mixed solution, the complexing agent is citric acid and glucose, wherein the molar ratio of citric acid: glucose: metal ion is 1:1:1, and ammonia water is added to adjust the pH value to 7, stirred in a water bath at 80°C for 3h, stirred at room temperature for 20h, aged for 48h, and a precursor solution with a certain viscosity of 0.9 Pa·s and a surface tension of 40mN / m is obtained.
[0058] (2) Air spinning
[0059] The precursor solution was used as a spinning solution for gas spinning, with a needle inner diameter of 1.5 mm, a syringe injection speed of 7 mL / h, an air atmosphere, an air flow rate of 200 L / min, and a collection distance of 200 cm to obtain a precursor fiber.
[0060] (3) Calcination treatment
[0061] The precursor fiber was pre-sintered at 200° C. for 1 h, and then calcined in air at 900° C. for 1 h at a heating rate of 5° C. / min to obtain a black fibrous LSCO conductive ceramic material.
[0062] Preparation of Ag / LSCO electrical contact materials
[0063] Silver powder and the above-mentioned fibrous LSCO conductive ceramic material are weighed in a mass ratio of 92:8, added into a ball mill, with a mass ratio of grinding balls to materials of 5:1, a rotation speed of 500 rpm, and mixed for 3 hours to obtain a silver-based composite material; after pressing and molding at 900 MPa, sintering is performed at a sintering temperature of 700°C and a holding time of 8 hours, and then re-pressing and re-firing are performed through the same pressing and sintering process to obtain an Ag / LSCO electrical contact material.
[0064] Control group
[0065] In this control group, sol-gel method was used to prepare granular La 0.5 Sr 0.5 CoO 3 The steps are:
[0066] (1) Preparation of precursor sol
[0067] Press La 3+ :Sr 2+ :Co 3+Lanthanum nitrate, strontium nitrate and cobalt nitrate were weighed in a molar ratio of 1:1:2, added into deionized water to prepare a mixed solution with a metal ion concentration of 0.5 mol / L, and magnetically stirred until completely dissolved; citric acid was weighed in a molar ratio of complexing agent citric acid to total metal ions of 2:1, and added into the mixed solution, and ammonia water was added to adjust the pH to 9, and stirred in a water bath at 80°C for 15 hours to obtain a wet gel.
[0068] (2) Calcination treatment
[0069] The wet gel was pretreated at 200 °C for 3 h to form a dry gel, which was then calcined in a muffle furnace. The specific calcination process was as follows: heating rate of 10 °C / min, holding temperature of 800 °C, holding time of 6 h, and finally granular La was obtained. 0.5 Sr 0.5 CoO 3 Powder.
[0070] Preparation of Ag / LSCO electrical contact materials
[0071] Silver powder and the above-mentioned granular LSCO conductive ceramic material are weighed in a mass ratio of 90:10, added into a ball mill, the mass ratio of grinding balls to materials is 4:1, the rotation speed is 300 rpm, and mixed for 4 hours to obtain a silver-based composite material; after pressing and molding at 1100 MPa, sintering is performed at a sintering temperature of 880°C and a holding time of 6 hours, and then re-pressing and re-firing are performed through the same pressing and sintering process to obtain Ag / LSCO electrical contact material.
[0072] The aspect ratios of the LSCO conductive ceramic fibers obtained in the above Examples 1-3 and the control group were calculated, and the corresponding resistivity and elongation after fracture of the reinforced silver-based composite materials were evaluated (see Table 1 for details).
[0073] Table 1 Characterization of electrical and mechanical properties of LSCO conductive ceramic fibers and their reinforced Ag-based composites
[0074]
[0075] After testing, the method of the present invention can obtain LSCO conductive ceramic fibers with controllable morphology and single phase (see Figure 1 , Figure 2). The fiber aspect ratio can be adjusted by changing the type of complexing agent, the water bath stirring temperature and the aging time. Polymers are no longer used as fiber forming agents, breaking through the limitation that polymers are "necessary" for gas spinning precursor solutions, greatly reducing costs and improving yields. Compared with granular LSCO conductive ceramic reinforced silver-based electrical contact materials, the fibrous LSCO conductive ceramic reinforced silver-based electrical contact materials obtained by the present invention have a lower resistivity and a larger elongation after break, that is, they have better conductive properties and are easy to process and suitable for industrial production. Therefore, the products prepared by the method of the present invention can be widely used in aerospace, new energy vehicles, high-power charging piles and other fields.
Claims
1. A fibrous La 1-x Sr x CoO 3-δ A method for preparing a conductive ceramic material, characterized in that: The following steps are involved: (1) Preparation of precursor solution by sol-gel method Press La 3+ :Sr 2+ :Co 3+ The molar ratio of the precursors is 1:1:2, 1:4:5 or 4:1:
5. The precursors are weighed and added into deionized water to prepare a mixed solution with a metal ion concentration of 0.5-2.0 mol / L, and stirred with a magnetic force until the solution is completely dissolved. Weigh the complexing agent according to the molar ratio of the complexing agent to the metal ion of 1-5:1, add it to the mixed solution, add ammonia water to adjust the pH value to 7-10, stir in a water bath at 50-80° C. for 3-10 hours, stir at room temperature for 10-20 hours, and age for 24-48 hours to obtain a precursor solution with a viscosity of 0.2-0.9 Pa·s and a surface tension of 30-40 mN / m; (2) Air spinning Using the precursor solution obtained in step (1) as a spinning solution for air spinning to obtain precursor fibers; (3) Calcination treatment The precursor fiber obtained in step (2) is pre-sintered and kept warm, and then calcined in air to obtain a black fiber-like La 1-x Sr x CoO 3-δ Conductive ceramic materials; The complexing agent in step (1) is one or more of maleic acid, acrylic acid, citric acid, and ethylenediaminetetraacetic acid; In step (3), the precursor fiber is pre-burned at a temperature of 150-200°C for 1-5 hours, and then calcined in air at a temperature of 700-900°C for 1-3 hours at a heating rate of 1-5°C / min.
2. The method according to claim 1, characterized in that La in step (1) 3+ , Sr 2+ 、Co 3+ The precursors are lanthanum nitrate, strontium nitrate and cobalt nitrate.
3. The method according to claim 1, characterized in that In the step (2), the inner diameter of the needle used in the air spinning is 0.1-1.5 mm, the syringe injection speed is 0.3-7 mL / h, the atmosphere is air, the air flow rate is 50-200 L / min, and the collection distance is 50-200 cm.
Citation Information
Patent Citations
Power-type nickel cobalt manganese acid lithium material as well as preparation method and application thereof
CN103811747A
Preparation method of Co-based spinel oxide nanowire
CN107164838A